Physiological and genetic aspects of a diploid potato population in the Netherlands and Northern Finland - Zaban, A.; Veteläinen, M.; Celis-Gamboa, C. B.; van Berloo, R.; Häggman, H.; Visser, R. G. (Suomen Maataloustieteellisen Seuran Tiedote, 2006)
Tuberization of potatoes exposed to different photoperiod regimes has been earlier investigated in several studies. However, there is still a limited understanding of the entire tuberization process and the factors influencing this process. One of the constraints of the previous studies has been the use of only one or a few genotypes. Furthermore, the experimental designs have not utilised the natural growing conditions with continuous changes in daylength during the growing season. The general aim of the project was to study the developmental dynamics of the broad-based potato (Solanum tuberosum L.) (CxE) population development at different climatical regimes under the very long-day, long-day and short conditions in Finland, the Netherlands and Ecuador/Venezuela, respectively. In this paper we are presenting some of the results achieved in the studies in Finland during the growing season 2004. In addition to population level trait characteristics we also describe here some of the identified QTLs (quantitative trait loci) for stolon related and tuber formation traits. In some cases we also compare the expression of some of the traits both in Finland and Netherlands.The main difference between the CxE population grown in Finland and the Netherlands was that the onset of flowering took place one week later in Finland. The relationship between tuber initiation and onset of flowering differed depending on the day length. In Finland approximately 70 % of the genotypes had swollen stolon tips before the onset of flowering, while in the Netherlands only 30 % of the genotypes had reached this condition. We also found numerous different trait linked QTLs, for example, a QTL associated with tuber formation was identified on chromosome E5, and QTLs associated with stolon characteristics on chromosomes E1, E4, E10 and E12. As a conclusion, the present preliminary results provide a good basis for determining the influence of different environmental conditions on potato development. In addition, the QTLs obtained in this study give a better understanding of the genetics of complex characters, and can be used in improving the potato crop in breeding programs.